Variables externas que infieren en el desgaste del pavimento flexible en vías de segundo orden del cantón guano. - Gualli Sáez, Jhonatan Paul (2025)
The analysis of external factors that affect the deterioration of flexible pavement is a crucial issue to ensure safety, comfort, transportation efficiency, reduced maintenance costs, and increased regional development. Road infrastructure is fundamental for economic development. However, climatic conditions, vehicular traffic, construction quality, and geotechnical characteristics affect the service life and performance. For this reason, research will be conducted using a mixed approach, combining qualitative and quantitative methodologies. This approach will involve visual inspections in representative sections of the road with critical failures in the flexible pavement, as well as an analysis of external variables that influence pavement deterioration. The analysis was carried out using statistical and correlation techniques with the help of software such as “EXCEL” and “POWER BI”, identifying the main factors that contribute to the irregular deterioration of the road. The results showed that critical failures are due to a lack of road awareness, defective materials, climatic conditions that accelerate road wear, poor design, material fatigue, and soil movement, among other factors. The analysis carried out with the help of the “POWER BI” software helped us to determine which failures have the greatest impact on second-order roads and to identify the main origin that leads to road wear, such as: constructive, geotechnical, human, age, and climate. The study provides us with valuable information to make decisions on road management and maintenance that should be carried out together with its supervision at the time of carrying out the construction of road infrastructure and thus apply preventive and corrective strategies to optimize public investment and ensure the safety of infrastructure and sustainability in the canton of Guano.